Ultrafast hardware-based focal law calculator for automatic focusing. (September 2015) - Cruza, Jorge F.; Camacho, Jorge; Moreno, Jose M.; Fritsch, Carlos
Abstract: Phased array ultrasonic imaging of arbitrarily shaped components at high scanning speed demands computing an adapted set of focal laws before each new image. This requires computing the individual time-of-flight (TOF) from array elements to foci in a two media scenario. Most precedent approaches to this problem were based on iterative search for the minimum TOF in a sampled interface (Fermat׳s principle). This work follows a different approach by implementing a specialized processor that performs TOF computations. Several algorithms are implemented using High Level Synthesis (HLS) for state-of-theart FPGAs: Fermat iterative search, Newton–Raphson, Illinois and a combination of the latter. Highlights: New Ultra Fast Focal-law calculation hardware and methods for NDT imaging. Three time-of-flight calculation algorithms implemented using HLS tools for FPGAs. A combination of Newton–Raphson and Illinois techniques gives the best results. HW implementation is very fast and fits in 20% of low-cost FPGA resources. A bound of the surface discretization step for iterative Fermat search is given.